The effect of high and low vowels on the fundamental frequency in singing: Some preliminary observations - Greiffenberg, Mette; Reinholt Petersen, Niels (Annual Report of the Institute of Phonetics University of Copenhagen, 2022)
Fundamental frequency was measured in high and low vowels in solo-singing. The effect of vowel height on Fo in singing was smaller than in speech, but it was shown to be highly significant. The results of a subsequent listening test indicated that listeners seemed to compensate perceptually for the inherent fundamental frequency differences when listening to solo-singing.